Advocacy for an institute of human studies - need to think beyond STEM - Mohanan, Tara, et al (Economic and Political Weekly)
India has been marching towards self-reliance in science, technology, engineering, mathematics and medicine disciplines; however, humanities and social sciences remain neglected. This article advocates the need for setting up a world-class institute for human studies that integrates scientific and humanistic pursuits, both pure and applied, with a focus on holistic development rooted in human values.- Reproduced